World Oceans Day, schools outreach event in Northern Ireland. - Nigel McDowell:::Creator::::::::::::
World Oceans Day 2019. Photograph of a schools outreach event in Northern Ireland with Our Lady of Lourdes and Ballymoney High School. World Oceans Day supports the implementation of worldwide Sustainable Development Goals and fosters public interest in the protection of the ocean and the sustainable management of its resources. Photograph and article "None of it is important or all of it is: Steinbeck, Ricketts, Ecology, and Identity," appear in Steinbeck Review, vol.16, no.2, 2022.